2014
DOI: 10.5194/bg-11-2519-2014
|View full text |Cite
|
Sign up to set email alerts
|

European sea bass, <i>Dicentrarchus labrax</i>, in a changing ocean

Abstract: Abstract. Ocean acidification, caused by rising concentrations of carbon dioxide (CO2), is widely considered to be a major global threat to marine ecosystems. To investigate the potential effects of ocean acidification on the early life stages of a commercially important fish species, European sea bass (Dicentrarchus labrax), 12 000 larvae were incubated from hatch through metamorphosis under a matrix of two temperatures (17 and 19 °C) and two seawater pCO2 levels (ambient and 1,000 μatm) and sampled regularly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…However, other species appear much more tolerant to the direct lethal effect of elevated p CO 2 , with no effect on larval survivorship reported in Baltic cod (Frommel, Schubert, Piatkowski, & Clemmesen, ), Atlantic herring (Franke & Clemmesen, ) and walleye pollock (Hurst, Fernandez, & Mathis, ). Survivorship even increased at 1,000 μatm p CO 2 in European sea bass (Pope et al., ). In winter flounder, there was a strong effect of elevated p CO 2 (≥1,800 μatm) on prehatching survival, but no effect on survivorship after hatching (Chambers et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other species appear much more tolerant to the direct lethal effect of elevated p CO 2 , with no effect on larval survivorship reported in Baltic cod (Frommel, Schubert, Piatkowski, & Clemmesen, ), Atlantic herring (Franke & Clemmesen, ) and walleye pollock (Hurst, Fernandez, & Mathis, ). Survivorship even increased at 1,000 μatm p CO 2 in European sea bass (Pope et al., ). In winter flounder, there was a strong effect of elevated p CO 2 (≥1,800 μatm) on prehatching survival, but no effect on survivorship after hatching (Chambers et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Fertilized D. labrax eggs from a mixed spawn (multiple males and females) were incubated in water at 19°C and 585 µatm p CO 2 (ambient) or 1000 µatm p CO 2 (for full details of rearing conditions, see the electronic supplementary material and Pope et al [24]); n  = 180 fish from 585 µatm p CO 2 conditions (mean length ± s.d. = 32.34 ± 3.12 mm), and n  = 90 fish (mean length ± s.d.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work continues to highlight the effects of secondary drivers such as ocean acidification, hypoxia and food availability on the capacity of an organism to adapt to changing temperatures and increasing numbers of recent studies are highlighting the interactive effects of temperature and secondary drivers (Vehmaa et al, 2013;Ko et al, 2014;Mackenzie et al, 2014b,c;Madeira et al, 2014;Pope et al, 2014). A recent study has demonstrated that trans-generational plasticity can mediate the effects of warming in a fish species (Shama et al, 2014); however, there remains low confidence in our understanding of the potential evolutionary adaptation to warming.…”
Section: Updates To Ar5mentioning
confidence: 99%